Bridging The Skills Gap: How Assessment Design, Industry Engagement, and Institutional Support Predict Employability Skills in Chinese Vocational Education - Xie, Dongna; Amiruddin, Mohd Hasril (Journal of Technical Education and Training, 2026)
This study investigated employability skills gaps between China's 1+X HR certificate graduates and employer expectations in Guangdong Province and identified factors predicting skills development. A convergent parallel mixed-methods design integrated quantitative surveys (n = 800: 400 graduates, 400 employers) with qualitative interviews (n = 15: graduates, employers, faculty). Independent samples t-tests compared graduate capabilities with employer expectations across nine competency dimensions. Confirmatory factor analysis validated measurement models, while structural equation modeling tested relationships between four predictors (self-efficacy, institutional support, industry engagement, and curriculum alignment) and employability skills. Thematic analysis of interviews explained quantitative patterns, with findings integrated through joint display matrices. All nine employability dimensions showed statistically significant gaps (p < .001) with large-to-very-large effect sizes (Cohen's d > 0.87). Professional HR Knowledge exhibited the largest gap (d = -0.998), followed by Digital Literacy (d = -0.952). The structural model explained 68.3% of variance in employability skills (R² = .683), with curriculum alignment demonstrating the strongest effect (? = .412, p < .001), followed by industry engagement (? = .298), self-efficacy (? = .251), and institutional support (? = .187). Qualitative findings revealed that 91% of certification examinations test memory recall rather than applied competencies; that curriculum content lags industry practice by 2-3 years; that institutional support varies dramatically across colleges; and that internship quality ranges from substantive to clerical. Mixed-methods integration demonstrated strong convergence between quantitative gaps and qualitative mechanisms. Findings recommend prioritizing performance-based assessment reform (?50% of certification scores), implementing dynamic curriculum update mechanisms, reducing revision lag from 24 to 6 months, standardizing institutional infrastructure quality, and ensuring substantive industry engagement through quality assurance protocols.